The Effect of Money Supply and Inflation on Banking Subsector Stock Prices During the 2020–2024 Period - Farhana, Baiq Indah; Ramadhani, Annisa Alifa (EAJ (Economic and Accounting Journal), 2025)
The 2020-2024 period was marked by the COVID-19 pandemic and economic recovery policies that caused fluctuations in the money supply, inflation, and stock prices, particularly in the banking subsector. This study aims to analyze the effect of the money supply and inflation on stock prices in the banking subsector using monthly data. The method used was quantitative with a total sampling technique on 16 banking companies listed on the Indonesia Stock Exchange (IDX). The analysis was conducted using panel data regression with the help of EViews 13 software. The results showed that the money supply and inflation had a positive and significant effect on stock prices, both partially and simultaneously. The model was able to explain 81.28% of the variation in stock prices through these two variables.